Designing E-Voting to Increase the Efficiency and Transparency of the Election of the OSIS Chairman at SMP Negeri 7 Prabumulih - Cindy Feronica Wulandari; Andi Christian; Nur Aini Hutagalung (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Cindy Feronica Wulandari (2021210014), Supervisor I Mr. Andi Christian S.kom., M.kom., and Supervisor II Ms. Nur Aini Hutagalung S.kom.M.,Si.,M.kom., entitled "Designing E-Voting Technology to Increase the Efficiency and Transparency of the Student Council President Election at SMP Negeri 7 Prabumulih." This research aims to design an Android-based e-voting application to increase the efficiency and transparency of the Student Council President election at SMP Negeri 7 Prabumulih. The manual voting process currently used has resulted in various obstacles such as counting errors, damaged ballots, and is time-consuming. Using the Rapid Application Development (RAD) method, this application was developed to make the voting and vote counting process faster, more accurate, and more secure, while encouraging active student participation in the school's democratic process. Therefore, it can be concluded that the Android-based e-voting application can increase the efficiency, transparency, and participation in the Student Council President election at SMP Negeri 7 Prabumulih, as well as simplify the digital voting and vote counting process.